Fiscal Decentralization and Regional Inequality: An Analysis of the Impact of Regional Autonomy on Inclusive Economic Growth - Ferizaldi, Ferizaldi (Nomico, 2026)
This study examines the impact of fiscal decentralization on regional inequality and inclusive economic growth in the context of regional autonomy. Fiscal decentralization is expected to enhance economic performance by allowing local governments to allocate resources more efficiently and respond to regional needs. However, its effectiveness in reducing inequality and promoting inclusive growth remains debatable. This research employs a quantitative approach with an explanatory design using panel data from multiple regions over a specified period. Data are collected from official government and statistical sources and analyzed using panel data regression models to assess the relationships between fiscal decentralization, regional inequality, and inclusive economic growth. The results indicate that fiscal decentralization has a positive and significant effect on inclusive economic growth, suggesting that greater fiscal autonomy supports regional economic development. However, it also has a positive impact on regional inequality, indicating that decentralization may widen disparities among regions. Furthermore, regional inequality is found to have a negative effect on inclusive economic growth, highlighting the importance of equitable development. In conclusion, fiscal decentralization can promote economic growth but does not automatically ensure inclusivity. Effective policy design, strong governance, and balanced fiscal capacity are essential to minimize inequality and achieve sustainable inclusive economic growth.